Pengaruh Perhatian Orang Tua dan Teman Sebaya terhadap Kecerdasan Interpersonal Siswa Kelas VII SMP Negeri 6 Ponorogo - Selvitia Putri Santika; Muhammad Ali (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to: (1) determine the significance of the influence of parental attention on interpersonal intelligence of seventh grade students at SMP Negeri 6 Ponorogo, (2) determine the significance of the influence of peers on interpersonal intelligence of seventh grade students at SMP Negeri 6 Ponorogo, (3) determine the significance of the influence between parental attention and peers on interpersonal intelligence of seventh grade students at SMP Negeri 6 Ponorogo. This research uses a quantitative method with an ex post facto type, whose data uses numbers. Data collection used a questionnaire, with Simple Random Sampling technique. The data analysis technique used is simple linear regression and multiple linear regression. Based on data analysis, the results found that: (1) Parental attention has a significant effect on the interpersonal intelligence of seventh grade students at SMP Negeri 6 Ponorogo, the amount of influence is 11.0%. (2) Peers do not significantly affect the interpersonal intelligence of seventh grade students of SMP Negeri 6 Ponorogo, (3) Parental attention and peers have a significant effect on the interpersonal intelligence of seventh grade students of SMP Negeri 6 Ponorogo the amount of influence is 11.6%. This research strengthens the theory of interpersonal intelligence by highlighting the role of social interaction, communication and cooperation in the development of students' interpersonal intelligence. The results of this study can be used as a reference for teachers to design, develop learning strategies that encourage positive interactions and collaboration between students. In addition, it can also help parents and schools create an environment that supports the development of children's interpersonal intelligence to the fullest.